Validation of Strategic Coaching Model for FlexIT-Pro Online-based Competency-based Education Program - Anthony, Peter; Fountain, Elizabeth; Takei, Hideki; White, Rachel; Williams, Luke (Journal of Education and Training, 2022)
Competency-based education (CBE) is a growing movement of higher education institutions to educate non-traditional adult learners. Coaching quality influences CBE's success as coaches share learning responsibility with students. FlexIT-Pro is a modified CBE program. After years of effective coaching, we developed a FITP Strategic Coaching Model and implemented it. This paper will present the Strategic Coaching Model, the assessment of the model, and the modified version of the model.